Numerical investigation on the combustion performance and emission formation of ammonia spark ignition engine using direct injection and multi coils spark-ignition strategy - Windarto, Cahyani; Utami, Indah Wahyu (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2025)
Future internal combustion engines can achieve zero carbon emissions by using ammonia, an efficient hydrogen energy carrier with a greater energy density and a more sophisticated production-storage-transportation lifecycle. Ammonia fuel's laminar flame speed is comparatively sluggish, nevertheless, which leads to less than ideal combustion performance. Investigating the impact of direct injection and the multi-coil method on ammonia spark ignition engine performance was the goal of this study. The simulation's output was then verified using standard diesel fuel and the literature on combustion performance for RCEM engines. At four SOIs between 40o and 0o BTDC, with varying multi-coil spark timing of ignition under high compression ratio of 17, the combustion performance and emission production of ammonia direct injection were examined using the created numerical model. As the timing of the spark increased, there was a tendency for the velocity and turbulence intensity to rise and then decline. Increased spark timing can improve ignition stability, reduce combustion time, reduce cooling loss, and boost output power. Ammonia flame propagation is sensitive to temperature and flow field. Regretfully, when the spark timing increases, the NOx emission progressively increases. By offering a basic ignition method for ammonia engines, this result holds promise for the transition of internal combustion engines to zero carbon ammonia engines.